PENGARUH UJARAN KEBENCIAN (HATE SPEECH) TENTANG PEMILIHAN GUBERNUR RIAU 2018 DI FACEBOOK TERHADAP OPINI MAHASISWA ILMU PEMERINTAHAN UNIVERSITAS RIAU - Sri Indah Desmarita; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract Hate speech is an act of communication carried out by an individual or group in the form of provocation, incitement, or insult to other individuals or groups in terms of various aspects. One example is the utterance of hatred that is spread through messages written on Facebook regarding the Candidate of the Governor of Riau 2018. In the S-R theory, it is stated that the attitude change process can occur if there is a stimulus that influences it. Based on this theory, researchers want to see how the effects of stimulus/utterance hate towards student responses / opinions. The method used is explanative quantitative using Slovin technique and the number of samples is 87 people. The researcher collected data with questionnaires. To process the test questionnaire data is done by using the SPSS Windows version 23 program. Based on the results of simple linear regression gets the value of regression coefficient in this r3esearch is Y = 5.843 + 0.432 X with a significance level of 0.000. of course ii’s smaller than α = 0.05. This means that there is the influence of hate speech about the election of the Governor of Riau 2018 on Facebook against the opinion of Riau University Government Science students at 59.7% and classified as the category of influence. While the remaining 40.3% is influenced by other variables not included in this study. Although not dominant, the respondents pay attention to the contents of the message delivered and arise from student opinion. So, Ho is rejected and Ha is accepted.